The Origins of Iconic Depictions: A Falsifiable Model Derived from the Visual Science of Palaeolithic Cave Art and World Rock Art. Issue 4 (3rd May 2018) - Hodgson, Derek; Pettitt, Paul
Abstract : Archaeologists have struggled for more than a century to explain why the first representational art of the Upper Palaeolithic arose and the reason for its precocious naturalism. Thanks to new data from various sites across Europe and further afield, as well as crucial insights from visual science, we may now be on the brink of bringing some clarity to this issue. In this paper, we assert that the main precursors of the first figurative art consisted of hand prints/stencils (among the Neanderthals and earlyHomo sapiens ) and a corpus of geometric marks as well as a hunting lifestyle and highly charged visual system for detecting animals in evocative environments. Unlike many foregoing arguments, the present one is falsifiable in that five critical, but verifiable, points are delineated.